A Computational Fluid Dynamics Model for the Small-Scale Dynamics of Wave, Ice Floe and Interstitial Grease Ice Interaction - Marquart, Rutger; Bogaers, Alfred; Skatulla, Sebastian; Alberello, Alberto; Toffoli, Alessandro; Schwarz, Carina; Vichi, Marcello (Fluids, 2021)
sponsorship: This research has been funded by the National Research Foundation of South Africa (Grant Nos. 104839, 105858 and 118745). Opinions expressed and conclusions arrived at are those of the author and are not necessarily to be attributed to the NRF. R.M., S.S. and M.V. acknowledge support from the South African National Antarctic Programme. A.A. and A.T. acknowledge support from the ACE Foundation-Ferring Pharmaceuticals and the Australian Antarctic Science Program (project 4434). AA is supported by the Japanese Society for the Promotion of Science (PE19055). (National Research Foundation of South Africa|104839, National Research Foundation of South Africa|105858, National Research Foundation of South Africa|118745, South African National Antarctic Programme, ACE Foundation-Ferring Pharmaceuticals, Australian Antarctic Science Program|4434, Japanese Society for the Promotion of Science|PE19055, Academy of Finland (AKA)|118745) status: Published